Core Strength Training Can Alter Neuromuscular and Biomechanical Risk Factors for Anterior Cruciate Ligament Injury. Issue 1 (January 2021) - Jeong, Jiyoung; Choi, Dai-Hyuk; Shin, Choongsoo S.
Background: Core stability is influential in the incidence of lower extremity injuries, including anterior cruciate ligament (ACL) injuries, but the effects of core strength training on the risk for ACL injury remain unclear. Hypothesis: Core muscle strength training increases the knee flexion angle, hamstring to quadriceps (H:Q) coactivation ratio, and vastus medialis to vastus lateralis (VM:VL) muscle activation ratio, as well as decreases the hip adduction, knee valgus, and tibial internal rotation angles. Study Design: Controlled laboratory study. Methods: A total of 48 male participants were recruited and randomly assigned to either the intervention group (n = 32) or the control group (n = 16). Three-dimensional trunk, hip, knee, and ankle kinematic data and muscle activations of selected trunk and lower extremity muscles were obtained while the participants performed side-step cutting. The core endurance scores were measured before and after training. Two-way analyses of variance were conducted for each dependent variable to determine the effects of 10 weeks of core strength training. Results: The trunk endurance scores in the intervention group significantly increased after training ( P < .05 for all comparisons). The intervention group showed decreased knee valgus ( P = .038) and hip adduction angles ( P = .032) but increased trunk flexion angle ( P = .018), rectus abdominis to erector spinae coactivation ratio ( P = .047), H:Q coactivation ratio ( P = .021), and VM:VL activation ratio ( P = .016). In addition, the knee valgus angle at initial contact was negatively correlated with the VM:VL activation ratio in the precontact phase ( R 2 = 0.188; P < .001) but was positively correlated with the hip adduction angle ( R 2 = 0.120; P < .005). No statistically significant differences were observed in the trunk endurance scores, kinematics, and muscle activations for the control group. Conclusion: Core strength training altered the motor control strategies and joint kinematics for the trunk and the lower extremity by increasing the trunk flexion angle, VM:VL activation ratio, and H:Q activation ratio and reducing the knee valgus and hip adduction angles. Clinical Relevance: Training core muscles can modify the biomechanics associated with ACL injuries in a side-step cutting task; thus, core strength training might be considered in ACL injury prevention programs to alter the lower extremity alignment in the frontal plane and muscle activations during sports-related tasks.